Juan Caramuel, Thanatosophia, y Nicolas Caussin - Sánchez Manzano, María Asunción (2020)
El discurso de Juan Caramuel titulado Thanatosophia resulta diferente de los libros devocionales sobre la preparación de la muerte. Para desarrollar esta temática, el autor siguió la técnica oratoria que había leído en De eloquentia sacra et humana de Nicolas Caussin. Este estudio revela la función de los elementos estructurales y estilísticos elegidos por Caramuel y analiza las referencias intertextuales entre estas dos obras para ofrecer una mejor comprensión de la Thanatosophia en su contexto cultural.
The speech by Juan Caramuel entitled Thanatosophia differs from devotional books on preparation for death. In order to treat this topic, the author followed the oratorial technique which he had read in De eloquentia sacra et prophana by Nicolas Caussin. This paper focuses on the function of the structural and stylistic elements chosen by Caramuel and analyses the intertextual references between these two works as a means of better understanding the Thanatosophia in its cultural context.
Keywords: Caramuel Lobkowitz, Juan, -- 1606-1682; Caussin, Nicolas, -- 1583-1651; Retórica -- 1601-1700; Oratoria -- 1601-1700